Certification of the efficient random number generation technique based on single‐photon detector arrays and time‐to‐digital converters - Andrea Stanco (Wiley, 2021)
Abstract True random number generators (TRNGs) allow the generation of true random bit sequences, guaranteeing the unpredictability and perfect balancing of the generated values. TRNGs can be realised from the sampling of quantum phenomena, for instance, the detection of single photons. Here, a recently proposed technique, which implements a quantum random number generator (QRNG) out of a device that was realised for a different scope, is further analysed and certified [1]. The combination of a CMOS single‐photon avalanche diode (SPAD) array, a high‐resolution time‐to‐digital converter (TDC) implemented on a field programmable gate array (FPGA), the exploitation of a single‐photon temporal degree of freedom, and an unbiased procedure provided by H. Zhou and J. Bruck [2, 3] allows the generation of true random bits with a high bitrate in a compact and easy‐to‐calibrate device. Indeed, the use of the ‘Zhou–Bruck’ method allows the removal of any correlation from the binary representation of decimal data. This perfectly fits with the usage of a device with non‐idealities like SPAD's afterpulses, pixel cross‐correlation, and time‐to‐digital converter non‐uniform conversion. In this work, an in‐depth analysis and certification of the technique presented in [1] is provided by processing the data with the NIST suite tests in order to prove the effectiveness and validity of this approach.